Penerapan Pembelajaran Berbasis Guided Discovery untuk Meningkatkan Keterampilan Proses Sains Peserta Didik Kelas VIII SMP Negeri 3 Pangkajene pada Materi Sistem Pencernaan - Riska Taruk Kendek; Nurhayani H. Muhiddin; Muhammad Aqil Rusli (Universitas Negeri Makassar, 2024)
This study aims to: (1) determine KPS level of students before and after implementation of guided discovery learning model class VIII SMPN 3 Pangkajene material digestive system; (2) knowing the increase KPS of students after applying guided discovery learning model class VIII SMPN 3 Pangkajene the digestive system material; (3) find out significant increase KPS after applying guided discovery learning model class VIII students SMPN 3 Pangkajene on the digestive system material. This research a pre-experimental study using One Group Pretest-Posttest Design. Population all students class VIII SMPN 3 Pangkajene. Sampling using saturated sampling technique. Instrument a multiple choice test. Data collection technique is giving pretest and posttest. Processing data using descriptive analysis techniques and inferential analysis. Based descriptive analysis, it was obtained that KPS N-gain score of students was 0.31 in medium category. Based results of inferential statistical analysis, it was obtained that Ho was rejected and H1 was accepted so that it was concluded there was an increase in the application guided discovery-based learning to improve the KPS class VIII students of SMPN 3 Pangkajene studying subject matter of digestive system.